A Study of SHA Plus Business Adoption of Social Media Using TOE Framework and Its Impact on Non-Financial Performance: An Empirical Study of Foodservice Sector in Chonburi Province, Thailand - Sakulsinlapakorn, Kongkidakarn (Asia Social Issues, 2024)
This study aims to investigate the TOE factors that positively influence social media adoption in SHA Plus businesses in the food service sector and examine the impact of social media adoption on non-financial performance. The study used a questionnaire survey to collect data from 300 Thai SHA Plus restaurants and used regression analysis for hypothesis testing. The findings suggest that technological, organizational, and environmental contexts are significant TOE factors that positively affect social media adoption in SHA Plus businesses. Moreover, after the implementation of social media, all non-financial performance factors, including innovativeness, competitive advantage, and customer satisfaction, are relatively significant in shaping the sustainable performance of the SHA Plus business. The study contributes to the literature on business practices and crisis management, providing practical implications for business owners and policymakers to adopt innovative practices and generate sustainability in SHA Plus non-financial performance. By identifying the critical TOE factors that influence social media adoption and the non-financial performance outcomes associated with social media adoption, this study can help SHA Plus businesses in the food service sector enhance their success in the business world.